Peramalan Kemasukan Penagih Dadah Wanita Ke Pusat Serenti Kemumin, Pengkalan Chepa, Kelantan - Rosland, Hussen (2002)
This study is a scientific analysis to forecast the inflow of female drug addict to Pusat Serenti Kemumin, Pengkalan Chepa, Kelantan from year 2002 to 2006. The objective of the study is to identify a suitable model as well as to identify a suitable model as well as to study the expected number admission of female drug addict within the duration. The four selected and tested model in the study is the Moving Average. Weighted Moving Average, Exponential Smoothing and Linear Regression. The smallest value of the Mean Squared Error (MSE) and Mean Absolute Deviation (MAD) will be chosen as most suitable method. The most suitable method is the Linear Regression. The study showed the inflow of female drug addict increase totally. Female drug addict admission that was classified as the new drug addict is also on an increase.